2004
DOI: 10.1021/ie030805q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Catalytic Activity by an Ion Product of Sub- and Supercritical Water in the Catalytic Hydration of Propylene with Metal Oxide

Abstract: We investigated the detailed mechanism of the relationship between the H+ concentration in the bulk phase and the activity of protonic acid sites on the catalytic surface. The theory clearly shows that the acidity of the catalytic surface is strongly affected by the change of the ion product in the bulk phase water. This phenomenon was apparent with other kinds of metal oxide catalysts and is largely caused by the change in the surface charge of the catalyst. In fact, through the kinetic analysis of the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Changes in physical and chemical properties of water under sub-critical conditions, especially in hydrogen bond, ion product and dielectric constant, could facilitate reactions with a wide range of organic compounds resulting in many useful materials. [1][2][3][4] One of the great challenges in the treatment of organic wastes is related to seafood wastes from seafood and fishery industries world wide. Prevention of marine pollution from dumping of organic wastes provided by the London treaty 5,6 of 1996 and other new environmental legislation restricted the disposal of these wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in physical and chemical properties of water under sub-critical conditions, especially in hydrogen bond, ion product and dielectric constant, could facilitate reactions with a wide range of organic compounds resulting in many useful materials. [1][2][3][4] One of the great challenges in the treatment of organic wastes is related to seafood wastes from seafood and fishery industries world wide. Prevention of marine pollution from dumping of organic wastes provided by the London treaty 5,6 of 1996 and other new environmental legislation restricted the disposal of these wastes.…”
Section: Introductionmentioning
confidence: 99%
“…17 Hence, the increment of pH pzc value of MgO/CH could be owing to the dispersion of MgO on the surface of CH. Higher pH pzc corresponds to higher basic character, 31 meaning that MgO/ CH had stronger basicity than CH. And it was confirmed by the next CO 2 -TPD analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the number of acid sites, Tomita et al , reported that the H + concentrations (the number of Brønsted acid sites) on MoO 3 /Al 2 O 3 and TiO 2 surfaces increased with increasing pressure; they used propylene hydration as the test reaction. They mentioned that water dissociation on the surface is promoted by a large K W at high pressures, which causes an increase in the H + concentration at the surface.…”
Section: Acid and Base Catalytic Properties Of Solid Catalysts In Sub...mentioning
confidence: 99%
“…Olefin hydration to alcohol in Sub&SCW is expected to proceed fast due to the high affinity of olefins to Sub&SCW. Reactions of propylene, , cyclohexene, and 1-octene ,, have been examined using solid acid catalysts. Further, the dehydration of alcohol to olefins, which is thermodynamically dominant at higher temperatures, was studied using 2-propanol, 2-butanol, and 2-octanol …”
Section: Reactions Catalyzed By Solid Acid/base Catalysts In Subandscwmentioning
confidence: 99%